Matthew's narrative portrait of disciples how the text-connoted reader is informed - Edwards, Richard Alan (Harrisburg, PA Trinity, 1997)
Includes bibliographical references.
Keywords: Bible. N.T. Matthew -- criticism,interpretation,etc